RETRACTED: Pseudomonas aeruginosa mucinous phenotypes and algUmucABD operon mutant characteristics obtained from inpatients with bronchiectasis and their correlation with acute aggravation - Tan, Yuxue; Dai, Zhongshang (Frontiers in Cellular and Infection Microbiology, 2024)
Objective Although the mechanism is unclear, Pseudomonas aeruginosa (PA) infection directly affects the frequency of acute exacerbations in patients with bronchiectasis. The purpose of this article is to analyze the genetic mutation characteristics of the algUmucABD operon in PA, isolated from hospitalized patients with bronchiectasis, and to explore independent risk factors for frequent acute exacerbations of bronchiectasis.Methods Based on the times of acute exacerbations occurred in the past year, these patients with bronchiectasis were divided into frequent acute exacerbations (Group A) and non-frequent acute exacerbations (Group B). We identified the distribution of mucoid phenotypes (MP) and alginate morphotypes (AM) in PA, and classified them into I -IV categories based on their different AM, otherwise, the gene mutation types (GMT) of the algUmucABD operon were tested. Subsequently, the relationship between GMT, MP, and AM, the independent risk factors for frequent acute exacerbations in patients with bronchiectasis were explored.Results A total of 93 patients and 75 PA strains, from January 2019 to August 2023, were included in this study. The MP and AM distributions of PA were as follows: 64 strains (85.33%) of mucoid (the AM were 38 strains of type Ⅰ, 3 strains of type Ⅱ, 23 strains of type Ⅳ), 11 strains of non-mucoid (the AM was type Ⅲ only). Mucoid PA with algU, mucA, mucB and mucD mutations accounted for 19.61%, 74.51%, 31.37% and 50.98%, respectively. GMT was divided into: mucA mutations only, mucA combined with other gene mutations, other gene mutations without mucA mutations, and without gene mutations. 91.7% of PA with type Ⅰ of AM occurred mucA mutations only, and in both separate MP and AM, the GMT differences were statistically significant. Lastly, the number of lung lobes with bronchiectasis and PA with mucA mutations only were the independent risk factors for frequent acute exacerbations.The mucA mutation was primarily responsible for the mucoid of MP and type Ⅰ of AM in PA, it was also an independent risk factor for bronchiectasis frequent exacerbations.